Bimbingan Karir Bagi Mahasiswa Jurusan Komputer untuk Fokus Pengembangan Diri Menghadapi Dunia Kerja - Priyudahari, Bhujangga Ayu Putu (Varied Knowledge Journal, 2024)
The rapid growth of job demands is accompanied by an increasing need for the improvement of human resources capabilities. Career guidance is an effort to enhance these capabilities through student counseling, including: (1) identifying interests and talents, (2) knowledge about types and career options, (3) knowledge about job requirements and types, (4) identifying career issues. This research is a qualitative descriptive study that captures the phenomena found in the career guidance learning process for fourth-semester Computer Education students at Musamus University, totaling 33 students. In this study, students were able to recognize their own abilities through self-analysis and identification, analyze local career opportunities relevant to their field of study, and then plan learning strategies to achieve their desired career goals. This demonstrates the necessity of career guidance in higher education institutions, providing students with an overview of the career opportunities available to them. This also contributes to increasing students' enthusiasm and motivation for their studies after understanding that education is a platform for developing skills and abilities that can be utilized in their careers.